2009
DOI: 10.21273/hortsci.44.6.1762
|View full text |Cite
|
Sign up to set email alerts
|

Dollar Spot Severity as Influenced by Fungicide Mode of Activity and Spray Nozzle

Abstract: Dollar spot, caused by Sclerotinia homoeocarpa, is a severe disease of highly maintained turfgrass. Improving the efficacy of fungicides when applied in relatively low water volumes may be possible through the optimization of nozzle selection. The objectives of this research were to evaluate fungicide efficacy when delivered through five different nozzle types and to elucidate any potential interactions between fungicide mode of activity and nozzle type. Research was conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…Fungicides and TE were applied using procedures shown to provide optimum dollar spot control on fairway height turf with a CO 2 -pressurized (276 kPa) sprayer equipped with an air-induction flat fan nozzle (AI9504E; TeeJet, Wheaton, IL) and calibrated to deliver water at 407 L · ha -1 (Couch, 1984;Kaminski and Fidanza, 2009;McDonald et al, 2006). All plots were mowed 1 d before dew removal and fungicide application and were mowed again 2 d after treatments.…”
Section: Methodsmentioning
confidence: 99%
“…Fungicides and TE were applied using procedures shown to provide optimum dollar spot control on fairway height turf with a CO 2 -pressurized (276 kPa) sprayer equipped with an air-induction flat fan nozzle (AI9504E; TeeJet, Wheaton, IL) and calibrated to deliver water at 407 L · ha -1 (Couch, 1984;Kaminski and Fidanza, 2009;McDonald et al, 2006). All plots were mowed 1 d before dew removal and fungicide application and were mowed again 2 d after treatments.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, Fidanza et al (2009) showed that nozzles delivering medium and coarse droplets increased chlorothalonil efficacy against dollar spot compared to fine and extra coarse droplets. Kaminski and Fidanza (2009) also determined that nozzle type influenced fungicide efficacy against dollar spot on fairways in areas with high disease pressure.…”
Section: Core Ideasmentioning
confidence: 99%
“…Proper water carrier volume and nozzle selection are crucial components in optimizing fungicide applications and maintaining acceptable turfgrass quality (Fidanza et al., 2009; Kaminski & Fidanza, 2009; Mattox et al., 2020; McDonald et al., 2006; Shepard et al., 2006). Mattox et al.…”
Section: Introductionmentioning
confidence: 99%
“…Two application factors that have been shown to impact the effectiveness of fungicides targeting turf diseases are spray volume and application timing (3,4,8). Nozzle type also can influence fungicide performance (7,8).…”
Section: Introductionmentioning
confidence: 99%